The Effect of Clearance Sale, Online Customer Review & Customer Experience on Purchase Decision at Indonesian Bagsdealer Stores, Tangerang - Mariati Dameria; Ike Kusdyah; Yunus Handoko (Jurnal Indonesia Sosial Teknologi, 2024)
Online shopping activities in Indonesia are carried out through marketplaces and social media. Since the COVID-19 pandemic in 2020, online shopping has become part of the daily lives of Indonesian people in various circles. Indonesian business circles looked at this opportunity, so various online stores appeared, including one of them is the Indonesian Bagsdealer Shop. The rise of online stores creates competition, and each tries to grab the interest of buyers. This study aims to analyze the influence of clearance sales, online customer reviews and customer experience on purchase decisions at Bagsdealer Indonesia Shop, Tangerang. This study uses a purposive sampling technique. The data collection instrument was in the form of a questionnaire (google form) on 145 respondents. The research data was processed quantitatively with multiple linear regression analysis techniques using SPSS version 26 software. The results of this study show that 1) clearance sale partially affects purchase decisions, 2) online customer reviews partially affect purchase decisions, 3) customer experience partially affects purchase decisions, and 4) clearance sales, online customer reviews, and customer experience simultaneously or together affect purchase decisions at Indonesian Bagsdealer stores as evidenced by an F value of 73.333 > F table 2.669 and significance values of 0.000 < 0.05.